A driving factor for harmful algal blooms in the East China Sea coastal marine ecosystems — Implications of Kuroshio subsurface water invasion. (August 2022) - Che, Hong; Zhang, Jing; Liu, Qian; Zhao, Meixun
Abstract: Quantitative calculation of the supply ratio of nutrients by different water masses suggests that the intrusion of Kuroshio subsurface water (KSSW) may indeed be an important factor in the formation of harmful algal blooms (HABs) in the Min-Zhe coastal area. This region in China has a complex hydrographic structure as well as a high incidence of HABs. The results of the calculations of the dissolved neodymium and its isotopes show that KSSW is an important provider of dissolved inorganic nitrogen (30–90 %) and phosphates (80–100 %) compared to the cases of the Taiwan Warm Current and the Changjiang Diluted Water. Sensitivity analysis results indicate that the percent contribution of KSSW in volume increased to 50–60 % in June, supplying favorable conditions for the growth of harmful algae. Our study implies that the invasion of the Kuroshio is likely to be a driving factor of HABs and, accordingly, a key factor in predicting HABs. Graphical abstract: Unlabelled Image Highlights: An isotope model was applied to evaluate the supply ratio of nutrients by water masses. KSSW is an important provider of dissolved inorganic nitrogen and phosphates. Contribution of nutrients from the TWC can be neglected although it is a key water mass in spring. Kuroshio is likely to be a driving factor for HABs in the East China Sea.